The Mitford murders - Fellowes, Jessica (Fellowes, Jessica. Mitford murders mystery., 2018)
It's 1920, and Louisa Cannon dreams of escaping her life of poverty in London. Louisa's salvation is a position within the Mitford household at Asthall Manor, in the Oxfordshire countryside. There she will become nursemaid, chaperone and confidante to the Mitford sisters, especially sixteen-year-old Nancy, an acerbic, bright young woman in love with stories. But then a nurse, Florence Nightingale Shore, goddaughter of her famous namesake, is killed on a train in broad daylight, and Louisa and Nancy find themselves entangled in the crimes of a murderer who will do anything to hide their secret.--Amazon.